BISTABILITY AND CYTOTOXICITY OF MEDICAL DEVICES BASED ON CROSS-LINKED BIOPOLYMERS - E. A. Nemets; A. P. Pankina; V. A. Surguchenko; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
The increase in biostability of medical products/materials based on proteins and their derivatives, including resorbable 2Dand 3D-matrices for tissue engineering and regenerative medicine is usually achieved by means of cross-linking with glutaraldehyde (GA). One of the serious fl aws of the products stabilized with GA is their cytotoxicity caused by trace amounts of GA which are diffi cult to remove from cross-linked biopolymer matrices, thus the search for chemical and physical methods of cross-linking of such medical products remains essential. Aim: to compare the infl uence of various cross-linking methods on the cytotoxicity of collagen and gelatin samples.Materials and methods. Samples – fi lms with diameter of 30 mm and thickness of ~ 150 μm, – were obtained by irrigation method usingthesolution of scleral collagen (SC) of Type farm animals or with gelatin with the subsequent drying at 37º С until constant weight on air. Samples of porous matrices in shape of tubes of gelatin and polyoxybutirate-co-valerate with the weight ratio 2:1 were obtained by electrospinning. The cytotoxicity of structurally stabilized samples was studied by fi ve methods: 1) dehydrothermal cross-linking with the residual pressure of 10–20 mm Hg and temperature of 120 °С; 2) injection of GA immediately into the biopolymer solution; 3) with GA vapors; 4) with GA vapors with the subsequent incubation in phosphate buffered saline (PBS) with рН = 7.4; 37 °С; 24 h; 5) with GA vapors with the subsequent incubation in 0.1% lysine solution with рН = 7.4; 37 °С; 24 hour in DMEM medium. Cytotoxicity of samples was evaluated according to the requirements of interstate standard GOST ISO 10993-5-2011 on the culture of mice fi broblasts of NIH 3Т3 line using extracts from samples (37 °С; 24 h) and by means of direct contact of samples with these cells.Results. Matrices treated hydrothermally demonstrated complete absence of cytotoxicity. Samples, fi xated in GA solution in the range of concentrations from 0.01 to 1.0% demonstrated a high level of cytotoxicity which does not answer the requirements of GOST ISO 10993-5-2011. Fixation of collagen and gelatin matrices with GA vapors during 48 h infl uences their cytotoxicity minimally but with the treatment time increased to 72 hours cytotoxicity escalates to severe levels. With the subsequent incubation of cytotoxic gelatin samples in PBS the decrease in cytotoxicity to the levels corresponding with the requirements of GOST ISO 10993-5-2011 was observed. For the analogous decrease in cytotoxicity of collagen fi lms treated with GA vapors during more than 48 h an additional incubation in lysine solution was needed.Conclusion. Dehydrothermal cross-linking method is optimal from the view point of absence of cytotoxicity of stabilized biopolymers, however its area of application is limited by the risk of infl uence of high temperatures on the medico-technical properties of the products. Fixation in GA vapors is a universally applicable and a rather simple method of treatment of medical products or biopolymer-based coatings, but it does not resolve the issue of their cytotoxicity at treatment times exceeding 48 h. Rinsing in buffer solution in case of gelatin or treatment with the amino acid (lysine) solution in case of collagen allow to decrease the level of cytotoxicity of products stabilized with GA vapors to the values corresponding with the requirements of GOST ISO 10993-5-2011.